PENGARUH KEPUASAN KERJA TERHADAP HUBUNGAN ANTARA IKLIM ORGANISASI DENGAN KINERJA PERAWAT PADA RSUD KOTA MATARAM - devi eka hartini; surati surati; hermanto hermanto (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2017)
This research is aimed at determining the effect of work satisfaction on the relation betweenorganizational atmosphere and performance of nurseat Mataram District Hospital. This research is an associative study. The datawerw collected through questionnaires, interview, and hospital as the population from which 162 nurses selected as the samples (besides 15 nurses were evaluated by the head of nurses). The were anlayzed using moderated regression analysis to test hipotesis. The research showed that there is significant and positive effect of organizational atmosphere and performance of nurses at Mataram District Hospitaal. The organizational atmosphere is good to boost the performance of the nurses. work satisfaction is not moderated variables but independent variable that affect the performance of the nurses of Mataram District Hospital. This means that work satisfaction directly affect the performance. The work satisfaction can make the relation between the work satisfaction and the performanceof the nurses but not significant enough. This mean that work satisfication does not affect significantly to strengthen the relation between the work satisfaction and the performance of the nurses, the relation of wihich is only 16,9%, while the rest is the effect of other vaariables outside the this research problemsKeywords: work satisfaction, organizational atmosphere, performance